2019
DOI: 10.18502/jdt.v15i6.325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence of Temporomandibular Joint Involvement in Rheumatoid Arthritis Using Research Diagnostic Criteria for Temporomandibular Disorders

Abstract: Objectives: Temporomandibular joint (TMJ) disorders, known as TMDs, are significant public health problems and may result in pain and disability. In order to determine the prevalence of clinical/subjective TMD in rheumatoid arthritis (RA), we used the research diagnostic criteria (RDC)/TMD axes. We assessed the anti-cyclic citrullinated protein (anti-CCP)-related TMD in RA for the first time.     Materials and Methods: Fifty-two RA patients were compared to 47 healthy controls with regard to complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
4
16
1
Order By: Relevance
“…However, we did not find any data regarding the possible relationship between salivary citrulline/ACPA and TMJ involvement. This finding is in accordance with reports previously published 18 , 19 , 33 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, we did not find any data regarding the possible relationship between salivary citrulline/ACPA and TMJ involvement. This finding is in accordance with reports previously published 18 , 19 , 33 .…”
Section: Discussionsupporting
confidence: 94%
“…We could just find a relationship between TMJ involvement and periodontal disease staging, which is somehow an obvious finding, as periodontal staging is based on MT, what is a risk factor for TMJ problems. Earlier there was a study, where significant relationship between serum anti-CCP and TMJ involvement was found 18 . However, we did not find any data regarding the possible relationship between salivary citrulline/ACPA and TMJ involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once temporomandibular joint (TMJ) is the unique synovial orofacial joint, it can be frequently affected in RA, including condylar and disc alterations 8 . However, literature is variable in reporting the frequency of temporomandibular disorder (TMD) due to RA [8][9][10] . Some authors found the presence of limited mouth opening 11 , TMJ pain 10,11 , muscular hyperactivity, and masticatory damage 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, literature is variable in reporting the frequency of temporomandibular disorder (TMD) due to RA [8][9][10] . Some authors found the presence of limited mouth opening 11 , TMJ pain 10,11 , muscular hyperactivity, and masticatory damage 12 . Still, some risk factors have been associated with the involvement of TMJ in patients with RA, as being of female gender, presence of mental disorders, insomnia or stroke 13 .…”
Section: Introductionmentioning
confidence: 99%